Crusades for Raw Materials. Circulation and Valorisation of Materials in Historical Discourse - Campailla , Carlo (E|C, 2023)
This paper aims to investigate the relationship between materials and historical discourse, through the semiotic analysis of a corpus of historical texts on raw materials and their history. This paper will focus on the role and the values that raw materials has had in relation to the social structure of each époque. According to the texts, the circulation of raw materials, new materials introduction or scarcity are crucial factors that determine fractures and remodulations of the whole social and historical context. However, this kind of description is deeply influenced by the theoretical viewpoint and the discoursive strategies that each text enacts.